Congenital lung malformations: radiological findings and clues for differential diagnosis. (November 2013) - Garcia-Peña, Pilar; Coma, Ana; Enríquez, Goya
Congenital lung malformations encompass a wide spectrum of conditions with a broadly varying clinical presentation. They are often a source of morbidity in infants and children. Their management depends on the type of malformation and its clinical presentation. Usually, the diagnosis requires an imaging evaluation. Classifications of bronchopulmonary malformations have undergone significant revision in recent years and several theories have attempted to explain their confusing pathogenesis. There are considerable degrees of overlapping and hybrid conditions are common, with interrelated malformations showing various radiologic and pathologic features. Attending to the pathophysiological mechanisms and structures involved, lung malformations can be divided into three categories: bronchopulmonary anomalies, combined lung and vascular abnormalities, and vascular anomalies. The purpose of this article is to review the current imaging techniques for evaluating lung malformations in pediatric patients and their characteristic imaging findings. Moreover, this review discusses a useful classification and offers some clues to facilitate the differential diagnosis.